Risk and Return Analysis of Stocks Listed on the Kuala Lumpur Stock Exchange's (KLSE) Main Board - Yusof, Za'imuddin (1997)
Relationship between risk and return of the stock in KLSE is important to the investor when making the selection decision for portfolio investment, Decision made weather to invest or not in particular stock depends greatly on investor's level of risk aversion and also the returns per unit of risk offered by the particular stock, Investor's ultimate goal is to maximise the gain or return from investment depends on how much risk is assumed, Construction of portfolio was use to diversify unsystematic risk of individual stocks to reduce the overall risk of portfolio but maintaining the return, This study is to analyse the relationship of risk and returns of stock listed on KLSE's Mainboard, The analysis was to determine whether portfolio construction can diversified unsystematic risk and which portfolio strategies to be use to construct efficient portfolio, The findings indicate that portfolio construction can diversify unsystematic risk, Portfolio by design strategy in portfolio construction was better in diversifying risk rather than using na'ive portfolio strategy,